Prevalence of psychiatric morbidities in two tertiary health institutions North west Nigeria: Assessing the realation to demographic variables - Bakare, Habeebah Toluwalase; Jimoh, AbdulGafar Olayiwola; Bakare, Abdulfatai Tomori (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
AbstractBackground: Mental illnesses constitute a significant fraction of the global burden of diseases. Currently evaluated at 11.5% and an expected burden of 15% by 2020, it accounts for 40% of the leading health conditions contributing to the disability adjusted life years (DALYS). Worldwide, 340 million people suffer from mental illnesses, the majority living in the developing world. The aim of this study therefore was to assess the prevalence and socio-demographic distribution of psychiatric disorders in the psychiatric outpatient department of two tertiary health institutions in Nigeria.Method: This was a descriptive cross-sectional study. All patients attending the psychiatric outpatient clinic of the two hospitals from January to June 2014, diagnosed with psychiatric disorders according to the diagnostic and statistical manual of mental disorders (DSM-5) were included in the study. The sample size was determined using single population proportion formula and 250 respondents were selected using systematic random sampling. Data was collected manually through proformas and analyzed using SPSS version 20.Result: The prevalent age group of persons with psychiatric disorders from this study was 21-30 years constituting 35.1% of respondents at FNPHK and 36% at UDUTH. In the rural hospital 57.3% of respondents diagnosed with psychiatric disorders were men while in the urban hospital 64% were women. Depression (38% and 25.5%) was the prevalent diagnosis. The leading primary psychiatric diagnosis in both institutions was comparable - depression, generalized seizure and schizophrenia. Conclusion: The prevalence of depression and schizophrenia is well documented in this study. The educational and geographic distribution of respondents suggests that high socio-economic status does not translate into less predisposal to psychiatric disorders. Policy makers and concerned government officials should enact and enforce laws that will help minimize associated social problems.